Emerging Markets in Transition : Growth Prospects and Challenges - Cubeddu, Luis (Staff Discussion Notes; Staff Discussion Notes ;, 2014)
After a short-lived slowdown in the immediate aftermath of the global financial crisis and a swift rebound, emerging markets (EM) are now entering a period of slower growth. In fact, growth is now lower than the post-crisis peak of 2010-11, as well as the rates seen in the decade before the crisis. This raises the question of whether EMs can bounce back to the growth rates seen in the last decade or whether their prospects are dimmer than thought a few years ago. This SDN we will explore the drivers of the slowdown, how changes in external conditions that supported high growth in EMs will affect them over the medium term, and the policy priorities needed to sustain the growth rates seen in the past decades. In doing so, the paper differentiates EMs along various dimensions (e.g. degree of commodity dependence, trade and financial openness) to highlight the need to tailor policy priorities.